Using Behavior-Analytic Treatment to Teach Tongue Lateralization Skills to Children With Avoidant/Restrictive Food Intake Disorder. (February 2023) - Phipps, Laura E.; Haney, Sarah D.; Zeleny, Jason; Andersen, Ashley S.; Peterson, Kathryn M.; Orloski, Stephanie
Oral-motor skills needed for efficient consumption of table-textured foods (e.g., tongue lateralization) often develop as children are exposed to food at increasingly higher textures (e.g., soft meltable, crunchy, and chewy; Volkert et al., 2014). For children with avoidant/restrictive food intake disorder (ARFID; American Psychiatric Association, 2013; World Health Organization, 2019), these oral-motor skills may not develop without intervention. We review case studies of three children diagnosed with ARFID who did not display the skills necessary for efficient consumption of regular table-textured food. We collaborated with a speech-language pathologist to identify oral-motor targets and used a behavior-analytic treatment to teach tongue lateralization skills necessary for safe and effective chewing. We used a treatment package consisting of nonremoval of the utensil with prompting and differential reinforcement to shape functional tongue movements. We discuss considerations for practitioners and the importance of individualized treatment and collaboration with other disciplines while teaching oral-motor skills necessary for chewing and consuming table-textured food.